PENGEMBANGAN STANDARISASI PENDIDIKAN DI PONDOK PESANTREN TERPADU AL KAMAL (PPTA) BLITAR - Muhammad Syahrul Munir; Miftahul Huda; Buhori Buhori; Efan Chairil Abdi (IAIN Pontianak, 2022)
Pondok Pesantren is a system of tafaqquh fiddin which needs to be supported by several components, both software, and hardware that support the existence of pesantren as a system. Al Kamal Blitar integrated Islamic boarding school (PPTA) is one of the Islamic boarding schools that was born before independence and continues to develop education by using the salaf, and khalaf system and synergizing with formal education. This study discusses the Standardization Development carried out at PPTA. So the purpose of this study was to see the form of development carried out by PPTA in standardizing education. This study uses a qualitative method with a descriptive form. The results of this study indicate that; 1) PPTA Blitar continues to develop standardization of Islamic boarding schools which include aspects; development of formal and non-formal educational institutions, standardization of teaching staff, and existing curriculum standards. 2) Standards for teaching staff must have standards by their respective scientific fields, while the curriculum standards used have also gone through an in-depth review process. 3) The process of developing educational standardization has been carried out by the integrated Al Kamal Islamic Boarding School for a relatively long period and has gone well.